P.007 Onset of facial weakness correlated with muscle strength in infantile facioscapulohumeral dystrophy (FSHD). (17th June 2016) - Mah, JK; Feng, J; Carty, C; Chen, Y; Duong, T
Abstract : Background: We investigated motor function associations with age, gender, and D4Z4 fragment size among participants with infantile FSHD. Methods: We collected standardized motor assessments including goniometry, manual muscle testing (MMT), quantitative muscle testing (QMT), and FSHD clinical severity scores (CSS) at 12 CINRG sites. To measure associations, we used linear regression models adjusted for age at enrollment, onset of weakness, gender, and D4Z4 repeats. Results: 53 participants (59% female, mean age 23.1±14.6 years) were enrolled. Weakness was most pronounced at the shoulder girdle and rectus abdominis (median MMT 30-38% of normal). Older enrollment age was associated with greater CSS (p=0.005) and reduced range of motion in shoulder abduction, shoulder flexion, elbow flexion, and ankle dorsiflexion (all p<0.01). Females and participants with larger D4Z4 repeats had milder shoulder/arm weakness and lesser disease severity (all p<0.05). Increased age at onset of facial weakness was significantly associated with greater total muscle strength, as measured by QMT and MMT (both p=0.002). Conclusions: We confirm the descending pattern of muscle involvement and milder disease severity in females or those with larger D4Z4 repeats. Furthermore, earlier age at onset of facial weakness was associated with greater muscle weakness. Future longitudinal assessments will describe rates of disease progression in this population.